2011
DOI: 10.1007/s11105-011-0331-4
|View full text |Cite
|
Sign up to set email alerts
|

Virus-Induced Gene Silencing of a Putative Glutathione S-Transferase Gene Compromised Ol-1-Mediated Resistance against Powdery Mildew in Tomato

Abstract: Previously, cDNA-amplified fragment length polymorphism analysis was used to profile differentially expressed transcript-derived fragments (DE-TDFs) of tomato between resistant and susceptible responses against the fungal pathogen Oidium neolycopersici. In the present study, we further investigated a DE-TDF annotated to a putative glutathione Stransferase (GST) that was more rapidly upregulated during the Ol-1-mediated resistance response than during the susceptible response. We used virus-induced gene silenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 30 publications
0
31
1
Order By: Relevance
“…Catalase activity increased mainly in moderately resistant genotype S. chmielewskii (L. chmielewskii); the increased concentration of free phenols was recorded during the first 120 h post inoculation in all three genotypes (S. lycopersicum, S. chmielewskii and S. habrochaites); but changes in lignification were not confirmed (Tománková et al 2006). Pei et al (2011) investigated the role of another important enzyme, glutation S-transferase in the pathogenesis process, specifically the Ol-1-mediated resistance response. They used virus-induced gene silencing to knock-down expression of the putative GST gene (ShGST) in resistant tomato plants (Solanum habrochiates G1.1560, formerly L. hirsutum) carrying the Ol-1 gene.…”
Section: Involvement and Activity Of Antioxidant Enzymes In Plant Sysmentioning
confidence: 99%
See 1 more Smart Citation
“…Catalase activity increased mainly in moderately resistant genotype S. chmielewskii (L. chmielewskii); the increased concentration of free phenols was recorded during the first 120 h post inoculation in all three genotypes (S. lycopersicum, S. chmielewskii and S. habrochaites); but changes in lignification were not confirmed (Tománková et al 2006). Pei et al (2011) investigated the role of another important enzyme, glutation S-transferase in the pathogenesis process, specifically the Ol-1-mediated resistance response. They used virus-induced gene silencing to knock-down expression of the putative GST gene (ShGST) in resistant tomato plants (Solanum habrochiates G1.1560, formerly L. hirsutum) carrying the Ol-1 gene.…”
Section: Involvement and Activity Of Antioxidant Enzymes In Plant Sysmentioning
confidence: 99%
“…The ShGST-silenced plants showed a susceptible phenotype after inoculation with O. neolycopersici. Microscopic observation demonstrated that O. neolycopersici was able to complete its life cycle on silenced resistant plants; however silencing of ShGST did not completely abolish the HR and hydrogen peroxide (H 2 O 2 ) accumulation (Pei et al 2011). …”
Section: Involvement and Activity Of Antioxidant Enzymes In Plant Sysmentioning
confidence: 99%
“…The GstA1 gene is specifically induced by fungal infection (Mauch & Dudler, 1993). GST is also required for resistance against O. neolycopersici in tomato (Pei et al, 2011). Glutathione has also been reported to be an important molecule for plant–pathogen resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Rar1, Rar2), as well as for mlo (Ror1 and Ror2) (Freialdenhoven et al 1994(Freialdenhoven et al , 1996Hückelhoven et al 2001). In tomato, silencing a putative glutathione Stransferase (GST) compromised the resistance conferred by the Ol-1 gene (Pei et al 2011). We are performing functional analysis of genes showing differential expression between MM and the NILs and expect to find different genes essential for specific Ol genes.…”
Section: Reprogramming Of Gene Expression Associated With Different Omentioning
confidence: 99%